Alva Ixtlilxochitl's Native archive and the circulation of knowledge in colonial Mexico - Brian, Amber, 1970- (Vanderbilt University Press, 2016)
"Focusing on the production and circulation of native knowledge through collaborations between Indigenous, mestizo, and creole intellectuals in colonial Mexico, this book proceeds through an in-depth case study of the exchange of Native materials between the family of don Fernando de Alva Ixtlilxochtil and don Carlos de Sigüenza y Góngora"--Provided by publisher.